Motives for Using Reddit Social Media on Members of the r/Indonesia Community - Galih Dwi Wicaksana; Candrasari, Yuli (HM Publisher, 2023)
The presence of social media provides many conveniences for its use. The many types of social media make the motives for using social media varied, and each individual has their own motives regarding the reasons for using social media. One of them is the social media Reddit. Reddit is a social media in the form of forum that was blocked by the Indonesian government in 2015. This study aims to find out the motives for using Reddit social media in Indonesia, especially for members of the largest Indonesian community on Reddit, namely the r/Indonesia community. This study uses Blumer's theory of motives for using social media and the concept of social media. The method used is qualitative with netnography techniques. Data were collected using in-depth interview techniques and participant observation. The informants in this study are Reddit social media users as well as members of the r/Indonesia community. The results obtained in this study are that the motives behind the use of Reddit social media are divided into three factors, namely motives to obtain information, motives for entertainment, and motives to avoid irrelevant information or spam.